2019
DOI: 10.1136/archdischild-2018-316240
|View full text |Cite
|
Sign up to set email alerts
|

Aeration strategy at birth influences the physiological response to surfactant in preterm lambs

Abstract: BackgroundThe influence of pressure strategies to promote lung aeration at birth on the subsequent physiological response to exogenous surfactant therapy has not been investigated.ObjectivesTo compare the effect of sustained inflation (SI) and a dynamic positive end-expiratory pressure (PEEP) manoeuvre at birth on the subsequent physiological response to exogenous surfactant therapy in preterm lambs.MethodsSteroid-exposed preterm lambs (124–127 days’ gestation; n=71) were randomly assigned from birth to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 35 publications
(116 reference statements)
6
36
0
Order By: Relevance
“…Aeration of the gasless fluid-filled lung is the critical event at birth, triggering the rapid changes in the respiratory and vascular systems necessary to adapt to extrauterine life. Aeration is a complex process dependent on several factors, including developmental and disease state of the lung (15), spontaneous breathing activity (24), expiratory braking (24), effective lung fluid reabsorption (1), effectiveness of positive pressure ventilatory support (15, 25b, 25c, 27, 28, 32), and/or pharma-cological treatments (2,30,33,34). Phase contrast X-ray imaging has shown that this process is initially driven by the transpulmonary pressure that first moves the fluid from the central airways to the lung periphery (10).…”
Section: Introductionmentioning
confidence: 99%
“…Aeration of the gasless fluid-filled lung is the critical event at birth, triggering the rapid changes in the respiratory and vascular systems necessary to adapt to extrauterine life. Aeration is a complex process dependent on several factors, including developmental and disease state of the lung (15), spontaneous breathing activity (24), expiratory braking (24), effective lung fluid reabsorption (1), effectiveness of positive pressure ventilatory support (15, 25b, 25c, 27, 28, 32), and/or pharma-cological treatments (2,30,33,34). Phase contrast X-ray imaging has shown that this process is initially driven by the transpulmonary pressure that first moves the fluid from the central airways to the lung periphery (10).…”
Section: Introductionmentioning
confidence: 99%
“…The specific aims of this study were to determine the independent effect of PEEP, tidal ventilation, and SI at birth on: 1) the volumetric conditions of the lung; and 2) subsequent early development of regional lung injury in the preterm lamb lung. Some of the results of these studies have been previously reported in abstract form (25), and some of the lambs have been used across other studies (26).…”
mentioning
confidence: 99%
“…The hypothesis that early application of "higher" PEEP levels could be beneficial is supported by animal data where higher PEEP levels (8-12 cmH 2 O) were more effective than lower levels in terms of gas exchange [12,13]. More recently, a dynamic increase of PEEP in preterm lambs (up to 14-20 cmH 2 O for 3 min) improved response to surfactant treatment and created a more uniform lung aeration, compared to positive pressure ventilation or SLI maneuvers [24]. Further evidence that higher pressure levels may decrease the need for invasive mechanical ventilation derives from studies using NIPPV as a mode of non-invasive respiratory support.…”
Section: Discussionmentioning
confidence: 95%